Em busca da comunicação significativa: Transformações no olhar de uma analista na clínica da inibição intelectual - Parente, Sonia Maria Berbare Albuquerque (2005)
In this work, I get the clinical experience developed within my professional life as an investigation object, focusing on the moments which guided to enlargements and / or to vertex changes in the direction of my clinical view. However, I intend to give visibility to used clinical devices, realized interventions and produced effects in the attendance of children with phychic suffering closed to moments and /or states of intellectual inhibition. The objective is to develop a reflection about the process of changing as to conceive and use Sara Paín and D.W.Winnicott s theoric referencials. Initially, the serious study in determined referencial allowed to assume its theory or aspects and, later, to be applied to a determined objective, verifying its efficacy or possibility of throwing light on some phenomenon aspect at stake. In my experience, the theory is useful and it interests when it serves to make clear the clinic I propose, therefore, a transicional use of the clinical theory. In the realized path, I could establish the relation between the intellectual inhibition and the theme of the significative communication, a conception which I inspired developed in the notion of Winnicott potential space. This conception revelead crucial in my clinical practice, for also having favored the overcoming of the children s difficulties and also for having disclosed how the ethinical bedding of my practice as analyst. The significative communication happens in the intersubjective therapeutical field, changing the subjectivity of the researcher-analyst into his clinical practice and in his understanding of the theories which use, at the same time that promotes the overcoming of the intellectual inhibition of the attended children.